Inventário documental da gestão de Gilberto Aquino Benetti: primeiro reitor eleito democraticamente na UFSM - Dias, Andressia Jociara (2019)
The present work presents a study about the documentary inventory of the management of the first Rector of the Federal University of Santa Maria (UFSM), democratically elected in the Institution, besides being the first student to arrive in office, in a period of redemocratization of the country, this documentation portrays a period relevant to the history of the country and the Institution. The research was established from the proposed objectives: to perform the documentary description of the documentary collection of The Management of Rector Gilberto Aquino Benetti (1985 - 1989), aiming to disseminate it through documentary inventory, in order to provide the access to documentary heritage and to redeem Institutional memory. In specific terms: describe the documentation; prepare a documentary inventory; recover the historical context of the management of Rector Gilberto Aquino Benetti; promote the dissemination of archival documentary heritage of the Permanent Archive Division (DAG/UFSM). This study is therefore justified by the documentation covering an important period the national and institutional history and should be treated by archival principles. Therefore, the description of the collection for later availability for research is essential for the rescue of institutional memory, dissemination of the collection custodian by the Permanent Archive Division (DAG) and valorization of UFSM's cultural heritage. Methodologically, the work is classified as a case study, with qualitative approach, descriptive objectives, and which made use of bibliographic survey techniques, documentary analysis, research to journalistic sources and the Information System of the National Archives (SIAN). The period of the redemocratization of Brazil was studied, with the purpose of understanding and verifying the reflections in the management of Gilberto Aquino Benetti in UFSM, marked by respect for direct elections, historical strikes, crisis in the Institution, and the search for consolidation of democracy. A diagnosis of the documentary situation of Gilberto Aquino Benetti's documentary collection, his typologies, storage, conservation, was made and interventions were made to identify, package, conservation and preservation of the collection. It was followed by the description of the documentary set of Gilberto Aquino Benetti's collection, which was carried out simultaneously to the preparation of the documentary inventory, and follows the mandatory elements of NOBRADE and the Classification Code and Temporality Table of UFSM documents. From the achievement of these steps, the final product of the master's thesis was obtained, the documentary inventory of Gilberto Aquino Benetti's Management at UFSM, which is the product resulting from this master's research, is available in Appendix B. Finally, the preservation of institutional memory and the appropriate access to UFSM's documentary heritage consists of the greater purpose of this research, aiming to value the institutional history, access and preservation of UFSM's cultural and documentary heritage.